E-Magazine Development of Tuberculosis and Stunting in Jungkat Village as an Instructional Tool in Body Defense System - Suvani, Monika Susi; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2025)
Magazines are widely known among teenagers but are still rarely found in the world of education. Content in magazines can also be considered to raise very important issues in society. Information on the relationship between tuberculosis and stunting, which is a problem in society, can be provided in learning through enrichment media in the form of e-magazines to be applied in learning about the structure and function of cells that make up tissue in the body's defense system in class XI high school. This research aims to develop an e-magazine about Immunity and TB and find out the results of the media developed for class XI SMA. The development of the e-magazine adapted the research and development (R&D) framework which refers to Borg and Gall which consists of 10 stages but is limited to the first 5 stages. Media validation was carried out by 5 validators, namely 2 lecturers and 3 high school teachers. Data analysis was carried out quantitatively by calculating the CVR and CVI values. The e-magazine media was successfully developed, and the initial product of this development was considered feasible with CVR and CVI values ​​= 1. The initial product in the form of e-magazine media is ready to proceed to the next development stage by first improving the graphic aspect, namely a clearer image display so that it is easier to understand. It is hoped that the products produced in this development research can motivate teachers to produce innovative media that is in line with technological developments